Pelatihan Pembenihan Ikan Papuyu (Anabas testudineus Bloch) di Desa Tabiku Kecamatan Seruyan Raya Kabupaten Seruyan: Training on Climbing Perch Hatchery (Anabas testudineus Bloch) in Tabiku Village, Seruyan Raya District, Seruyan Regency - Pangestu, Mustaqiim; Najamuddin, Anang; Suraya, Ummi; Yusuf, Noor Syarifuddin; Rozik, Muhammad (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Climbing Perch (Anabas testudineus Bloch) is a freshwater fish that inhabits swamps, rivers, lakes, and other water bodies. Some communities have begun cultivating climbing perch but still lack information on breeding techniques, leading to reliance on wild-caught fry. This community service activity, conducted by the Fisheries Department of the University of Palangka Raya in collaboration with the Tabiku Village Government, was to provide training on climbing perch breeding. This initiative aimed to encourage the community to engage in climbing perch hatchery businesses and improve the quality of climbing perch fry. The method used in this community service program was a participatory approach to climbing perch breeding. This included socialization, theoretical sessions on hatchery techniques, and hands-on training in various breeding activities. These activities covered fish spawning techniques, pond preparation, broodstock selection, spawning process, feeding, and fry harvesting. Five pairs of broodstock were used with a male-to-female ratio of 3:1. As a result of this program, approximately 25.000 eggs were produced, with an 85% hatching rate. The fertilization rate of papuyu fish eggs was 78%, resulting in 16.575 larvae. During the rearing period, 1.320 fry measuring 3–5 cm were obtained using a 4x6 meter tarpaulin pond. To improve the survival rate of climbing perch fry, increasing the number of nursery ponds for better fry development is recommended.